Evaluasi Program - Program Strategis Pemerintah Kota Bandung Di Bidang Ekonomi dalam Upaya Penguatan dan Peningkatan Kemampuan Daya Beli Masyarakat : Suatu Tinjauan Analisis Kebijakan Publik - Bayu Kharisma (Jurnal Manajemen Teori dan Terapan, 2016)
This study aims to evaluate and prioritize the various forms of strategic programs at the Bandung City Government in strengthening the economy and increasing purchasing power of the people in the city of Bandung based on public policy analysis. This study is comprehensive covering macro aspects, namely the potential and economic profile as well as the Human Development Index (HDI) and micro aspects, namely the external and internal environmental analysis relating to economic policy on purchasing power. Furthermore, evaluation and economic policy priorities in an effort to increase the purchasing power of the city of Bandung.